2016
DOI: 10.1016/j.ibiod.2016.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of azo dye methyl red by suspended and co-immobilized bacterial cells with mediators anthraquinone-2,6-disulfonate and Fe3O4 nanoparticles

Abstract: a b s t r a c tIn this study, the decolorization and degradation of methyl red (MR) by suspended and immobilized cells of Aeromonas jandaei strain SCS5 under anaerobic and aerobic conditions have been investigated. The complete decolorization of MR at a concentration of 100 mg L À1 by A. jandaei strain SCS5 was obtained within 6 h for both anaerobic and aerobic suspended cultures, where the decolorization rate was faster in acidic conditions than basic conditions. The decolorization efficiency under 6 h increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 47 publications
1
22
0
3
Order By: Relevance
“…The formation of highly stable AgNPs was visually confirmed by the appearance of yellow color and further verified by the existence of surface plasmon resonance (SPR) peak around 425 nm. Sharma et al (2016) have studied decolorization and degradation of Methyl Red by suspended and immobilized cells of Aeromonas jandaei strain SCS5 under anaerobic and aerobic conditions. The complete decolorization of Methyl Red at a concentration of 100 mg l -1 by A. jandaei strain SCS5 was recorded within 6 h for both anaerobic and aerobic suspended cultures, but the decolorization rate was faster in acidic than basic P.K.…”
Section: Role Of Nanotechnology In Decolorization and Degradation Of mentioning
confidence: 99%
“…The formation of highly stable AgNPs was visually confirmed by the appearance of yellow color and further verified by the existence of surface plasmon resonance (SPR) peak around 425 nm. Sharma et al (2016) have studied decolorization and degradation of Methyl Red by suspended and immobilized cells of Aeromonas jandaei strain SCS5 under anaerobic and aerobic conditions. The complete decolorization of Methyl Red at a concentration of 100 mg l -1 by A. jandaei strain SCS5 was recorded within 6 h for both anaerobic and aerobic suspended cultures, but the decolorization rate was faster in acidic than basic P.K.…”
Section: Role Of Nanotechnology In Decolorization and Degradation Of mentioning
confidence: 99%
“…Previous studies have reported decolorization of azo dye methyl red (MR) using microbial strain. For example, a recent study has reported decolorization of azo dye MR using immobilized bacterial cells of Aeromonas jandaei (Sharma et al, 2016). Zhao et al, have also reported the biodegradation of MR by Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Ademais, algumas tecnologias envolvidas no tratamento físico-químico destes efluentes, e.g. membranas e meios filtrantes, possuem alto custo (Dos Santos et al, 2007;Sharma et al, 2016). A degradação biológica de azo-corantes tem sido estudada por vários autores pela premissa de oferecer uma solução mais sustentável do ponto de vista econômico e de produção de resíduos, além do seu potencial de reduzir ou até mesmo eliminar a toxicidade desses efluentes.…”
Section: Tratamento Biológico De Efluentes Da Indústria Têxtilunclassified
“…As aminas aromáticas e outros intermediários gerados no processo de descoloração redutiva são recalcitrantes ao tratamento anaeróbio, de modo que muitos autores optam por um pós-tratamento aeróbio para remoção destes compostos (Amaral et al, 2014;Amorim et al, 2013;Braúna et al, 2009;Gavazza et al, 2015;Imran et al, 2016;Sharma et al, 2016;Talarposhti et al, 2001). A aplicação de aeração intermitente para a remoção de cor, que será testada neste estudo, é uma alternativa aos processos convencionais anaeróbio-aeróbios e visa à descoloração e biodegradação de metabólitos no mesmo compartimento reacional.…”
Section: Aeração Intermitente Aplicada à Biodegradação De Aminas Aromunclassified
See 1 more Smart Citation